If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 6 = 4x + 24 Reorder the terms: 6 + 2x = 4x + 24 Reorder the terms: 6 + 2x = 24 + 4x Solving 6 + 2x = 24 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 6 + 2x + -4x = 24 + 4x + -4x Combine like terms: 2x + -4x = -2x 6 + -2x = 24 + 4x + -4x Combine like terms: 4x + -4x = 0 6 + -2x = 24 + 0 6 + -2x = 24 Add '-6' to each side of the equation. 6 + -6 + -2x = 24 + -6 Combine like terms: 6 + -6 = 0 0 + -2x = 24 + -6 -2x = 24 + -6 Combine like terms: 24 + -6 = 18 -2x = 18 Divide each side by '-2'. x = -9 Simplifying x = -9
| -6+(-6)x=-42 | | x+3/2=9/2 | | 18t+11v=w-3t | | -3(x-4)=-24 | | 1+k=12.3 | | 5t+2=13 | | 39+9x=102 | | x=x^2+4x-1 | | (w-1)(2w+3)=5 | | (4x-30)=(3x+10) | | 7x-7=9x-15 | | 15=5(x-9) | | -6-6x=48 | | 45=-25+7x | | 3*3*3*3*3=9*9 | | 22-3g+5forg=4 | | 9.1+y=4.3 | | (2x-11)+3=16 | | 61+10x=-29 | | 3(3+0.9t)=2(-2.4t-3) | | 30-6x=60-26x | | 8-3(x-2)=2 | | 6x+8x=7x-14 | | 11+8x=59 | | 5z-8=3+7z | | 6x^2-x+1=2 | | 3x-37=6x+50 | | 10n-2n=4 | | 66-2x=75-3x | | x-1.22x=3.5 | | -3x+42=6x-129 | | 0.02x+1.5=2 |